2009
DOI: 10.1127/0935-1221/2009/0021-1897
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyenes in the coloration of cultured freshwater pearls

Abstract: The exact nature of pigments present in cultured freshwater pearls is still not well known. We examined 21 untreated cultured freshwater pearls from Hyriopsis of typical colors by diffuse reflectance UV-Vis-NIR and Raman scattering measurements, at high resolution. The objective was to establish the relation between color and the nature of the pigment mixture in pearls, using strictly non-destructive methods. All natural color samples show the two major Raman resonance features of unmethylated (unsubstituted) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 29 publications
5
65
1
Order By: Relevance
“…The ingestion of pigment-enriched microalgae potentially leads to an accumulation of pigments in mollusk tissues and the shell (Soldatov et al, 2013). On the other hand, it has been argued that polyenes do not generate from food sources like other pigments (i.e., carotenoids), but they are locally synthesized (Karampelas et al, 2009). In accordance to Stemmer and Nehrke (2014), the results presented here support the view that the specific diets on which the animals rely on do not influence shell pigment composition.…”
Section: Environmental Influence On Shell Microstructuresupporting
confidence: 77%
See 1 more Smart Citation
“…The ingestion of pigment-enriched microalgae potentially leads to an accumulation of pigments in mollusk tissues and the shell (Soldatov et al, 2013). On the other hand, it has been argued that polyenes do not generate from food sources like other pigments (i.e., carotenoids), but they are locally synthesized (Karampelas et al, 2009). In accordance to Stemmer and Nehrke (2014), the results presented here support the view that the specific diets on which the animals rely on do not influence shell pigment composition.…”
Section: Environmental Influence On Shell Microstructuresupporting
confidence: 77%
“…Furthermore, an enrichment in polyenes has been observed in the growth lines, potentially indicating their involvement in the biomineralization process (Stemmer and Nehrke, 2014). However, the specific functions of these organic compounds have not been disclosed yet (Hedegaard et al, 2006;Karampelas et al, 2009). Given the high phenotypic variation in pigmentation among and within mollusk species, it has been proposed that coloration does not have a primary function as an adaptive tool (i.e., camouflage, warning signaling) as in other animals (Seilacher, 1972;Evans et al, 2009).…”
Section: A Islandica Shell Organizationmentioning
confidence: 99%
“…[21,25]. Previous works from Maia et al [27,29] and comparison with the literature data [13] have demonstrated that the red octocoral L. punicea may contain 11 conjugated double bonds due to the presence of ν(C=C) modes at ca 1509 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In this way, under resonance or pre-resonance conditions (λ 0 = 632.8 nm), there is clearly a preferred signal enhancement for the bands at 1504 and 1150 cm −1 . This effect, known as the resonance Raman effect, can also be used for the study of several conjugated polyenes present in the most different samples, such as corals [25,49], the shells of molluscs [24], pearls [21,50], plants [41], etc. It is also clear that the presence of the band at 1008 cm −1 , related to the δ(C−CH 3 ) mode, occurs as one of the enhanced modes in the Raman spectra of carotenoids, according to figure 4, in which it can be seen in the spectrum of pure astaxanthin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation